KARAKTERISTIK TEMPAT PERINDUKAN DAN KEPADATAN JENTIK NYAMUK Aedes aegypti - Shodikin, R.Firwandri Marza (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2016)
The breeding places of Aedes aegypti mosquito is generally in the form of shady places where stagnant water. Water where mosquitoes lay their eggs should be clean water or water that is not directly in contact with the ground. People who still use a reservoir of water for daily use can allow the breeding of mosquitoes in the area. Breeding places have characteristics such as type, location, presence of cover and volume. The purpose of this study was to determine the characteristics and density of mosquito breeding places of Aedes aegypti in RW 03 Gurun Laweh of Nanggalo in 2016. This research was used a descriptive study design and data collection conducted in RW 03, Gurun Laweh Nanggalo on 16 May to 3 June 2016, the way the sampling is done Proportional Random Sampling 101 homes. The collection of data by observation using tools such as checklists and processing of computerized data with univariate analysis. Results of the study is the kind of breeding sites is the most common landfill (78%). Location of breeding sites in homes (78.8%). Breeding sites without cover (94.8%) and the breeding sites of small volume (73.6%). Figures House Index (HI) of 27.7%, a figure Container Index (CI) was 17.2%, a figure Breteau Index (BI) of 42.5 and Free Larvae Indicators (ABJ) of 72.3%. If the results are compared with the Density Figure, the number of HI, CI and BI obtained show moderate density. We recommend that people need to monitor a reservoir of water as breeding places of Aedes aegypti and more attention to cleanliness around the house and like draining a reservoir of water (1 x week), close the water reservoirs, buried scrap items that can become breeding places of mosquitoes. Keywords : Aedes aegypti, characteristics of breeding places, density